Making Art – Taking Part! Negotiating participation and the playful opening of liminal spaces in a collaborative process - Zobl, Elke; Huber, Laila (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
How can we open participatory spaces playfully and critically? Our article raises this question in the context of a research project at the intersection of participatory and interventionist art, critical art education and participatory research. In the project “Making Art – Taking Part!” (www.takingpart.at), which the authors, along with additional team members, conducted with students aged 14–16 in Salzburg, Austria, an artistic intervention in public space was developed based on the ideas, experiences, and desires of the students. In a collaborative process, we explored strategies for self-empowerment, deconstruction of established knowledge and power relations, and appropriation by artistic and art mediation means around the topic of “living together”. In this paper, we argue that by employing such strategies, a liminal space can be opened – in a playful, yet critical way – in which the meaning of participation is collaboratively negotiated.